Tackling social inequality in development : beyond access to appropriation of ICTs for employability - Loh, Yvonne Ai-Chi (2019)
This study was motivated to investigate social inequality in developed nations, by studying the impact of ICTs upon the vulnerable unemployed and under-employed in Singapore. First, drawing upon Amartya Sen’s capability approach, we operationalize the dependent variable as self-perceived employability, conceptualized as both a measure of well-being and a livelihood capability. Secondly, we used Neil Selwyn’s digital divide hierarchical impact assessment framework, to define and measure the ICT assets of access, usage, and appropriation. Primary data was gathered from 302 under-employed and unemployed workers in Singapore, a developed Asian economy. Regression analyses revealed that higher-order hierarchies of ICT usage and appropriation were associated with the dependent variable of employability, while access was not. We discuss the implications for development discourse in regions with ubiquitous access, advocating for policymakers to focus on ICT training. Further, we offer nuanced findings on vulnerability in developed economies as an enhancement to mainstream ICT4D scholarship, focused exclusively on poverty in developing countries.